2006
DOI: 10.1007/s00414-006-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Y-STR analysis of degraded DNA using reduced-size amplicons

Abstract: To increase the success rate of Y-STR genotyping for degraded DNA, we have developed two multiplex PCR sets for 21 Y-STR loci. Besides the 17 Y-STR loci of DYS19, DYS385, DYS389-I, DYS389-II, DYS390, DYS391, DYS392, DYS393, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635, and GATA H4.1 contained in a commercial Y-STR kit, AmpFlSTR Yfiler, the other four loci of DYS388, DYS446, DYS447, and DYS449 were also included in the multiplexes to increase the discrimination capacity. Among a total of 21 Y-STR loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Because of environmental destruction and the scarcity of forensic samples, incomplete Y-STR profiles are often obtained from trace evidence material or mixed male/female samples in forensic casework. The DYS19, DYS389II, DYS448, and DYS635 loci have been reported to be among the most frequent noninformative loci, followed by DYS385a/b, DYS390, DYS392, DYS437, and DYS438 in the 17 Y-STRs system [6,14,15]. Loss of the signals will decrease the discrimination capacity.…”
Section: Introductionmentioning
confidence: 95%
“…Because of environmental destruction and the scarcity of forensic samples, incomplete Y-STR profiles are often obtained from trace evidence material or mixed male/female samples in forensic casework. The DYS19, DYS389II, DYS448, and DYS635 loci have been reported to be among the most frequent noninformative loci, followed by DYS385a/b, DYS390, DYS392, DYS437, and DYS438 in the 17 Y-STRs system [6,14,15]. Loss of the signals will decrease the discrimination capacity.…”
Section: Introductionmentioning
confidence: 95%
“…The problem with which forensic scientists have recently been confronted involves the technical difficulty of analyzing degraded DNA samples. In recent years, several papers have demonstrated that short amplicon STR (miniSTR) represents one of the most useful tools for analyzing degraded DNA samples [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. On the other hand, given Y-STRs role as a characteristic feature of haploid paternal inheritance without recombination, analysis of Y-STR plays a major role in male personal identification, deficiency paternity cases including male relatives, and male profiling for sexual assaults involving male-female stain mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, allelic and haplotypic frequencies of Y-STRs should be determined in a male population prior to any interpretations of forensic analysis and paternity testing [6,[8][9][10][11]19]. In this study, allelic and haplotypic frequent-cies involving 10 Y-STR loci: 8 Y-STR loci as recommended by Y Chromosome Consortium (YCC) plus DYS388 and YCAIIa/b-have been determined with such a necessity in a representative group of Turkish population in order to make comparisons with other populations.…”
Section: Introductionmentioning
confidence: 99%